Pelatihan Penulisan Artikel Ilmiah untuk Meningkatkan Kompetensi Pendidik di SMKS Nurul Huda Pringsewu - Irawan, Agus; Ipnuwati, Sri; Mukodimah, Siti (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2024)
Scientific article writing training is one way to enhance educators' ability to conduct research and publish scientific works. This program was held at SMKS Nurul Huda Pringsewu with the primary goal of improving educators' skills in writing scientific articles in accordance with applicable standards and regulations. The training includes several stages, such as material presentation, writing workshops, and individual guidance. The results of the training show a significant improvement in understanding and skills in writing scientific articles among the participants. Additionally, the educators who participated in this training became more motivated to conduct research and publish their findings. Therefore, this training is expected to have a positive impact on the development of educators' professionalism and the improvement of education quality at SMKS Nurul Huda Pringsewu